Preparation and Dating of Mortar Samples—Mortar Dating Inter-Comparison Study (MODIS). Issue 6 (10th November 2017) - Hajdas, Irka; Lindroos, Alf; Heinemeier, Jan; Ringbom, Åsa; Marzaioli, Fabio; Terrasi, Filippo; Passariello, Isabella; Capano, Manuela; Artioli, Gilberto; Addis, Anna; Secco, Michele; Michalska, Danuta; et al.
Abstract: Seven radiocarbon laboratories: Åbo/Aarhus, CIRCE, CIRCe, ETHZ, Poznań, RICH, and Milano-Bicocca performed separation of carbonaceous fractions suitable for 14 C dating of four mortar samples selected for the MOrtar Dating Inter-comparison Study (MODIS). In addition, optically stimulated luminescence (OSL) analyses were completed by Milano-Bicocca and IRAMAT-CRP2A Bordeaux. Each laboratory performed separation according to laboratory protocol. Results of this first intercomparison show that even though consistent 14 C ages were obtained by different laboratories, two mortars yielded ages different than expected from the archaeological context.